Permeability Prediction in Deep Coal Seam: A Case Study on the No. 3 Coal Seam of the Southern Qinshui Basin in China - Pinkun Guo; Yuanping Cheng (The Scientific World Journal)
The coal permeability is an important parameter in mine methane control and coal bed methane (CBM) exploitation, which determines the practicability of methane extraction. Permeability prediction in deep coal seam plays a significant role in evaluating the practicability of CBM exploitation. The coal permeability depends on the coal fractures controlled by strata stress, gas pressure, and strata temperature which change with depth. The effect of the strata stress, gas pressure, and strata temperature on the coal (the coal matrix and fracture) under triaxial stress and strain conditions was studied. Then we got the change of coal porosity with strata stress, gas pressure, and strata temperature and established a coal permeability model under tri-axial stress and strain conditions. The permeability of the No. 3 coal seam of the Southern Qinshui Basin in China was predicted, which is consistent with that tested in the field. The effect of the sorption swelling on porosity (permeability) firstly increases rapidly and then slowly with the increase of depth. However, the effect of thermal expansion and effective stress compression on porosity (permeability) increases linearly with the increase of depth. The most effective way to improve the permeability in exploiting CBM or extracting methane is to reduce the effective stress.